The overlap between autistic spectrum conditions and borderline personality disorder. - Robert B Dudas; Chris Lovejoy; Sarah Cassidy; Carrie Allison; Paula Smith; Simon Baron-Cohen (PLoS ONE, 2017)
Background Both people with autism spectrum conditions (ASC) and borderline personality disorder (BPD) are significantly challenged in terms of understanding and responding to emotions and in interpersonal functioning. Aims To compare ASC, BPD, and comorbid patients in terms of autistic traits, empathy, and systemizing. Methods 624 ASC, 23 BPD, and 16 comorbid (ASC+BPD) patients, and 2,081 neurotypical controls (NC) filled in the Autism Spectrum Quotient (AQ), the Empathy Quotient (EQ) and the Systemizing Quotient-Revised (SQ-R). Results On the AQ, the comorbid group scored higher than the ASC group, who in turn scored higher than the BPD group, who scored higher than controls. On the EQ, we found the comorbid and ASC groups scored lower than the BPD group, who were not different from controls. Finally, on the SQ-R, we found the ASC and BPD group both scored higher than controls. Conclusions Similar to ASC, BPD patients have elevated autistic traits and a strong drive to systemize, suggesting an overlap between BPD and ASC.